2002
DOI: 10.1093/tropej/48.6.377
|View full text |Cite
|
Sign up to set email alerts
|

Increased Heights and Weights of Isfahani Female Children and Adolescents in Iran

Abstract: Considering the different patterns of growth in various societies, an anthropometric evaluation of 6-18-year-old female students was carried out in 1997 in Isfahan, Iran with the goal of establishing height and weight values for use in clinical settings. 4638 female Isfahani students aged 6-18 years were selected by a random cluster sampling. Their height (cm) and weight (kg) were measured and the related percentiles were determined. The results were compared with previous studies in Iran using Student's t-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Ayatollahi (1993) reviewed previous studies of human growth in Iran and compared them with his findings on primary school children in Shiraz and concluded that children were bigger than they had been 20 years ago. Aminorroaya and colleagues (2002) have observed that during 1976 to 1997, the weight and height of 10–14‐year‐old girls in Isfahan had increased by 1–4 kg and 6–12 cm, respectively. These reports could not be generalized to the entire population of Iran because they had either small sample sizes or were based on children attending clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Ayatollahi (1993) reviewed previous studies of human growth in Iran and compared them with his findings on primary school children in Shiraz and concluded that children were bigger than they had been 20 years ago. Aminorroaya and colleagues (2002) have observed that during 1976 to 1997, the weight and height of 10–14‐year‐old girls in Isfahan had increased by 1–4 kg and 6–12 cm, respectively. These reports could not be generalized to the entire population of Iran because they had either small sample sizes or were based on children attending clinics.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, data from Aminorroaya et al (2002) reveal that the height curves of 6-to 17-year-old female students from Iran can almost be superimposed on those of the CDC/NCHS growth charts, but the American girls were significantly taller than Iranian girls after age 14. The growth patterns among Iranian students, however, had improved when compared with those of their fellow citizens from 22 years earlier.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that centiles derived from the data were substantially below US data in both sexes and concluded that the use of locally based growth charts was essential for assessing the growth of children in Iran. In 1997, Aminorroaya et al (2003) conducted a survey on 4364 male students of 6-18 years of age in Isfahan, the third biggest city of Iran in the central part of the country. They noted that their results were comparable with US data.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that their results were comparable with US data. They also evaluated 4638 2-18-year-old female students and showed that girls' height curves could be approximately superposed on those of US growth charts, but US girls were significantly heavier than Isfahan girls after the age of 14 (Aminorroaya et al 2002). As a whole, although the discrepancy among the results might be because of outdated data, it reveals a need for local standards, especially when results from different areas of Iran differ from each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation